1995
DOI: 10.1016/0378-1097(95)00037-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of trichlorophenols by Alcaligenes eutrophus JMP134

Abstract: The degradation of chlorophenols by Alcaligenes eutrophus JMP134 (pJP4) was studied. The strain grew on 2,4,6-trichlorophenol or 2,4,6-tribromophenol as the sole carbon and energy source. Complete degradation of 2,4,6-trichlorophenol was confirmed by chloride release and gas chromatography analysis of supernatants from growth cultures. The 2,3,5-, 2,3,4-, 2,3,6- and 2,4,5-isomers of trichlorophenol did not support growth. However, up to 40% of 2,4,5-trichlorophenol was mineralized during growth of A. eutrophus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 5 publications
1
38
0
Order By: Relevance
“…strain C964 (6). Several 2,4,6-TCP-degrading bacteria have been reported (1,2,6,9,10,25,30,42,45). Recently, Clement et al (10) have shown that Ralstonia eutropha JMP134 and JMP222 (which does not harbor the 2,4-dichlorophenoxyacetic acid-degrading plasmid pJP4) grow on 2,4,6-TCP as the sole carbon source.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…strain C964 (6). Several 2,4,6-TCP-degrading bacteria have been reported (1,2,6,9,10,25,30,42,45). Recently, Clement et al (10) have shown that Ralstonia eutropha JMP134 and JMP222 (which does not harbor the 2,4-dichlorophenoxyacetic acid-degrading plasmid pJP4) grow on 2,4,6-TCP as the sole carbon source.…”
mentioning
confidence: 99%
“…Several 2,4,6-TCP-degrading bacteria have been reported (1,2,6,9,10,25,30,42,45). Recently, Clement et al (10) have shown that Ralstonia eutropha JMP134 and JMP222 (which does not harbor the 2,4-dichlorophenoxyacetic acid-degrading plasmid pJP4) grow on 2,4,6-TCP as the sole carbon source. The reported cell yields for JMP134 and JMP222 growing on only 2,4,6-TCP are extremely low, and the culture's turbidity at 660 nm reaches a maximum of 0.043 after 5 days of incubation (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the contribution of tfdCI was critical to prevent the accumulation of the toxic metabolite chlorocatechol. Both JMP134 (pJP4) and its cured derivative, JMP222, are able to grow on 2,4,6-trichlorophenol (TCP), suggesting that that pathway for TCP degradation is chromosomally encoded (16). However, while JMP222 can only grow with concentrations of TCP of up to 0.2 mM, JMP134(pJP4) can easily tolerate up to 0.5 mM TCP.…”
Section: Biodegradation Of Herbicides Pesticides and Antimicrobialsmentioning
confidence: 99%
“…These compounds can be accumulated or, otherwise, further metabolised through the ortho, modified ring-cleavage pathway . One extensively studied example of an efficient chloroaromatic degrading bacteria that use such a chlorocatechol degradation pathway is Ralstonia eutropha JMP134 (pJP4), a strain able to grow on 2,4-dichlorophenoxyacetate (2,4-D), and 3-chlorobenzoate (3-CB), as well as other chloroaromatics (Don and Pemberton, 1981;Pieper et al 1988;Clément et al 1995). Most of its catabolic abilities are encoded on the tfd genes from the plasmid pJP4 (Figure 1a).…”
mentioning
confidence: 99%